Leukocytoclastic Vasculitis Associated with Nintedanib in Idiopathic Pulmonary Fibrosis: A Case Report - Çebi, Işıl; Yılmaz, Meltem (The European Research Journal, 2026)
Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial lung disease. Nintedanib, a tyrosine kinase inhibitor, is one of the approved antifibrotic agents used in IPF treatment. While gastrointestinal side effects are common, cutaneous vasculitic reactions are extremely rare. We report a 70-year-old male with IPF, diagnosed by a radiological usual interstitial pneumonia pattern, who developed leukocytoclastic vasculitis (LCV) ten days after initiation of nintedanib therapy. The patient presented with palpable purpura on both lower extremities, accompanied by abdominal pain and diarrhea. Laboratory tests were unremarkable, and a skin biopsy confirmed LCV. Nintedanib was discontinued, and treatment with oral prednisolone resulted in the resolution of the lesions. Antifibrotic therapy was subsequently switched to pirfenidone. To our knowledge, this is the first reported case of nintedanib-associated LCV. Physicians should be aware of this rare adverse reaction in IPF patients receiving nintedanib.